2017
DOI: 10.1123/jpah.2016-0656
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Schoolyard Intervention Targeting Children’s Recess Physical Activity and Sedentary Behavior: Effects After 1 Year

Abstract: The multicomponent schoolyard PA intervention was effective in making children spend a larger proportion of recess time in light PA, which was most likely the result of a shift from sedentary behavior to light PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
14
1
1
Order By: Relevance
“…This result is in accordance with previous studies (10, 1820). An increase in MVPA is in contrast to VanKann's intervention study (13) that showed positive LPA outcomes but no effect on MVPA. In a review, Ickes et al (21) reported that a variety of recess interventions has been found to be effective in increasing PA.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…This result is in accordance with previous studies (10, 1820). An increase in MVPA is in contrast to VanKann's intervention study (13) that showed positive LPA outcomes but no effect on MVPA. In a review, Ickes et al (21) reported that a variety of recess interventions has been found to be effective in increasing PA.…”
Section: Discussioncontrasting
confidence: 75%
“…To our knowledge, few studies have investigated sustained effects of school-based intervention on PA (10, 13, 23). Ridgers et al (10) demonstrated a positive effect on MVPA and vigorous physical activity (VPA), but the PA levels were lower at 12 months compared with 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations